Ozone therapy and restorative dentistry: a literature review - A. O. Arigbede; O. O. Dosumu; O. P. Shaba (Nigerian Dental Association, 2010)
Objective: Over the recent years, restorative dentistry has shifted towards practicing preventive dentistry and adopting more conservative and tooth-preserving procedures. This approach is being further reinforced with the emergence of ozone therapy in the management of tooth decay. Ozone therapy is the treatment of the tooth with a mixture of oxygen and ozone. The aim of this review was to provide a comprehensive literature on ozone therapy and on the different areas of restorative dental specialty where this emerging treatment alternative has been found applicable. Method: The Medline and Google databases were searched for relevant literature using the following terms "ozone therapy and dentistry", "ozone", "atraumatic tooth restoration", "tooth decay and remineralization". Manual library search and review of bibliographies of published literature were also conducted. Publications that discussed what ozone therapy is all about, the history, mechanism of action, production of ozone, toxicity and clinical applications particularly in Restorative Dentistry were extracted. Result: Ozone therapy causes remineralization of incipient pit and fissure caries as well as incipient root caries. Its usefulness in open lesions has also being demonstrated. Dental decay may sometimes be managed without the conventional anaesthetic, drill and filling. It is also used in Restorative Dentistry for sterilization of removable dentures and avulsed tooth, tooth bleaching and desensitization. There is conflicting evidence regarding its application in endodontics at the moment. Conclusion: There is some demonstrable emerging evidence to suggest that ozone therapy is useful in restorative dentistry and it could turn around for good the practice of the discipline in the near future. Its mode of application in dentistry ensures its safety.